Subendocardial viability ratio, ambulatory blood pressure monitoring and serum biomarkers for cardiovascular disease in chronic kidney patients - Nejc Piko; Tajda Šrot; Nina Hojs; Sebastjan Bevc; Radovan Hojs; Robert Ekart (Acta Medico-Biotechnica, 2021)
Purpose: Chronic kidney disease (CKD) is associated with a higher prevalence of cardiovascular diseases. The pulse wave analysis measures the aortic pressure waveform based on noninvasive peripheral pressure recording. The subendocardial viability ratio, as part of the pulse wave analysis, is a noninvasivemeasure of microvascular coronary perfusion.Methods: In the present study, we investigated the relationship between the subendocardial viability ratio, 24-h ambulatory blood pressure measurements, and serum biomarkers to determine the risk for cardiovascular disease in patients with CKD. A pulse wave analysis using applanation tonometry was performed in 86 patients with CKD. Serum biomarkers were measured in patients, and the patients were grouped according to the median value of the subendocardial viability ratio.Results: The mean age of the patients was 60 ± 13 years; 65% of the patients were men, and the mean subendocardial viability ratio was 151% ± 34%. Patients with CKD in the lower subendocardial viability ratio group (<151%) had significantly lower hemoglobin (p=0.002) and higher NT-proBNP (p=0.034), serum phosphorus (p=0.04), augmentation index (p=0.003), 24-h pulse (p=0.004), and 24-h pulse pressure(p=0.003).Conclusion: Our findings suggest that patients with CKD with a subendocardial viability ratio below 151% have a higher cardiovascular risk.